Bone Marrow-Liver-Spleen Type of Large B-Cell Lymphoma Associated with Hemophagocytic Syndrome: A Rare Aggressive Extranodal Lymphoma - Kirill A. Lyapichev; Jennifer R. Chapman; Oleksii Iakymenko; Offiong F. Ikpatt; Uygar Teomete; Sandra Patricia Sanchez; Francisco Vega (Case Reports in Hematology)
Recently, an unusual subtype of large B-cell lymphoma (LBCL) with distinctive clinicopathologic features has been recognized; it is characterized by involvement of bone marrow with or without liver and/or spleen, but no lymph node or other extranodal sites, usually associated with fever, anemia, and hemophagocytic lymphohistiocytosis (HLH). Because of this distinctive clinical presentation, it has been designated “bone marrow-liver-spleen” (BLS) type of LBCL. To date there is only one series of 11 cases of BLS type of LBCL with detailed clinical, pathologic, and cytogenetic data. Herein, we describe a case of BLS type LBCL presenting with associated HLH in a 73-year-old female. The bone marrow core biopsy showed cytologically atypical large lymphoma cells present in a scattered interstitial distribution and hemophagocytosis and infrequent large lymphoma cells were seen in the bone marrow aspirate smears. Circulating lymphoma cells were not seen in the peripheral blood smears. The patient underwent treatment with chemotherapy (R-CHOP) but unfortunately passed away 2 months after initial presentation. BLS type of LBCL is a very rare and clinically aggressive lymphoma whose identification may be delayed by clinicians and hematopathologists due to its unusual clinical presentation and pathologic features.